A experiência de ser mãe e os desafios frente à carreira e à separação do bebê - Beltrame, Greyce Rocha (Universidade do Vale do Rio dos Sinos, 2012)
This Master's thesis pursues to deepen the experience of being a mother today, meeting the demands required for women both in public and the importance of their presence in baby's life. Thus, this work provides thoughts about women who reconcile motherhood and work, focusing on mothers who are experiencing the moment of separation from their babies for the option to reinvest in career after the end of maternity leave period. For this, it was presented a theoretical paper that talks about the value assigned to motherhood over three centuries, including changes in the mother’s role from the women’s entry into labor market and articulating the issues motherhood and career. Based on the understanding that psychoanalysis gives necessary psychic transformations for mother to turn to mother-infant relationship, in the initial moments of baby’s life, the second study is presented. It is an empirical paper that aims to understand the experience of motherhood related to separation from first-born child in baby’s adjustment period at school of early childhood education, owing to the end of maternity leave period and the return to work. It was realized a qualitative research using Multiple Case Study approach. The participants of this study were four first-time mothers who were passing through baby’s adjustment period at Early Childhood Education School because of their return to work by the end of maternity leave. Through interviews and genogram of the family, results show the value that participants attribute to their work, as well 9 as the conflict of mothers who know their duties with babies, but they feel most appropriate at workplace. It is also explored mother’s view about school as an environment that enables baby’s socialization, and strategies to balance mother and career roles. It is considered that the present thesis can contribute to a broadening on reflections about woman’ role as a mother in contemporary society, paving the way for improvement and discussion with people who are responsible for baby’s care in early childhood, toward to prevention and intervention at early childhood education school, which it is understood as a new place of subjectivity.
Keywords: Maternidade; Trabalho; Escola de educação infantil; Bebê; Motherhood; Work; Early childhood education school; Baby; ACCNPQ::Ciências Humanas::Psicologia